Robust Adaptive Beamforming Algorithm Using Instantaneous Direction of Arrival with Enhanced Noise Suppression Capability - Yoon, Byung-Jun; Tashev, Ivan; Acero, Alex (Proceedings of International Conference on Audio, Speech and Signal Processing ICASSP 2007, 2007)
In this paper, we propose a novel adaptive beamforming algorithm with enhanced noise suppression capability. The proposed algorithm incorporates the sound-source presence probability into the adaptive blocking matrix, which is estimated based on the instantaneous direction of arrival of the input signals and voice activity detection. The proposed algorithm guarantees robustness to steering vector errors without imposing ad hoc constraints on the adaptive filter coefficients. It can provide good suppression performance for both directional interference signals as well as isotropic ambient noise. For in-car environment the proposed beamformer shows SNR improvement up to 12 dB without using an additional noise suppressor.